Ice as a granular material - Turnbull, Barbara; Swift, Michael; Hill, Richard (2016)
Ice is a unique material, fundamental to vital processes on earth, in the atmosphere [1] and as planets and comets form [2]. In this work, we introduce two experiments investigating ice as a granular material, to provide snippets of insight into those processes. Initial investigations of ice particles in a granular flow show that the energy spent in collisions can generate localised surface wetting, even below the melting point [3]. This wetting reduces friction between granules, leading to acceleration of the bulk flow and in turn more wetting. The experiments described here are designed to show how even wetting invisible to an observer, can fundamentally alter the flow. The experiments also use the diamagnetic properties of ice to investigate how the outcome of high speed binary collisions, energetic enough to generate some melting, depends on this wetting.